Relationship between consumer involvement and consumer engagement with consumer loyalty in tourism and hospitality industry - Leong, Mei Kei; Osman, Syuhaily; Paim, Laily (Human Resource Management Academic Research Society, 2017)
Economic growth has seen in the tourism and hospitality industry and competition in this industry has caused in discovering consumer loyalty as a key success factor. Consumer loyalty can raise the business’s value and maintain a long term relationship between the consumers and company. In this review, consumer involvement is identified as the independent variable and able to influence consumer loyalty. Furthermore, the newly emerged term of consumer engagement acts as the mediator of the relationship between consumer involvement and consumer loyalty. This review paper proposed that these three constructs are interrelated. Besides that, due to the widely used of term involvement, engagement and loyalty, this study explores the complexity of the multi-dimensions and dynamic nature of the constructs. The purpose of this study is to review published journals on consumer involvement, consumer engagement and consumer loyalty to better understand its evolution and development especially in tourism and hospitality industry. Besides that, the theories and its application were also discussed. The theory that is suitable to the current research paper is Service Dominant Logic theory while the supporting foundations are Consumer Engagement Model, Consumer Involvement Profile, and 3H’s Model. This review on previous published materials also found out that linkage between the variables exists. Besides that, the dimensionalities of consumer involvement and consumer engagement were found to have varies sets of dimensions. Thus, selecting suitable dimensionality in representing the constructs is essential to gain a reliable result. The main conclusion drawn from this review is that consumer involvement and consumer engagement are able to influence consumer loyalty in tourism and hospitality industry. The contributions of current paper and implications for future researchers were discussed.